THE PENGARUH IMPLEMENTASI KEBIJAKAN DIKLATPIM POLA BARU DAN KOMPETENSI KEPEMIMPINAN MO’ODELO TERHADAP KUALITAS PELAYANAN PUBLIK DI PEMERINTAH PROVINSI GORONTALO - Irfan Ibrahim (Politeknik STIA LAN Makassar, 2019)
The purpose of this study was to investigate the effect of the improved leadership training program designed for lower level public service managers on the quality of public service in which the local wosdom of Mo’odelo leadership was treated as an intervening variable. This research employed a qualtitative approach using an explanatory survey technique. Data were collected through questionnaires and interviews. The were analysed using PLS (Partial Least Square) technique with the help of SmartPLS 3.1 software. The population consisted of lower level managers within the Gorontalo Provincial Government and ASN personnel at the Gorontalo Province Training Agency amounting to 520 people. Eighty-four sample respondets were drawn from the population. The results showed that: (1) the Newly improved leadership program for lower level did not directly affect on Public Services Quality; (2) the effect of the new leadership program on Public Services quality was mediated by indigenous Leadership Competency called Mo’odelo. This study therefore recommends that Gorontalo Provincial Government should complement the leadership development program with Mo'odelo as local wisdom if the objective is to include improvement of public service quality.